Phase I/IIa study of intratumoral/intracerebral or intravenous/intracerebral administration of Parvovirus H-1 (ParvOryx) in patients with progressive primary or recurrent glioblastoma multiforme: ParvOryx01 protocol - Geletneky, Karsten; Hüsing, Johannes; Knebel Doeberitz, Magnus von; Hajda, Jacek (BMC cancer, 2012)
The treatment of patients with malignant brain tumors remains a major oncological problem. The median survival of patients with glioblastoma multiforme (GBM), the most malignant type, is only 15 months after initial diagnosis and even less after tumor recurrence. Improvements of standard treatment including surgery and radio-chemotherapy have not lead to major improvements. Therefore, alternative therapeutics such as oncolytic viruses that specifically target and destroy cancer cells are under investigation. Preclinical data of oncolytic parvovirus H-1 (H-1PV) infection of glioma cells demonstrated strong cytotoxic and oncosuppressing effects, leading to a phase I/IIa trial of H-1PV in patients with recurrent GBM (ParvOryx01). ParvOryx01 is the first trial with a replication competent oncolytic virus in Germany.